Iron, Oxidative Stress, and Metabolic Dysfunction—Associated Steatotic Liver Disease - Sophie Gensluckner; Bernhard Wernly; Christian Datz; Elmar Aigner (Antioxidants, 2024)
Excess free iron is a substrate for the formation of reactive oxygen species (ROS), thereby augmenting oxidative stress. Oxidative stress is a well-established cause of organ damage in the liver, the main site of iron storage. Ferroptosis, an iron-dependent mechanism of regulated cell death, has recently been gaining attention in the development of organ damage and the progression of liver disease. We therefore summarize the main mechanisms of iron metabolism, its close connection to oxidative stress and ferroptosis, and its particular relevance to disease mechanisms in metabolic-dysfunction-associated fatty liver disease and potential targets for therapy from a clinical perspective.